f(x) = x^2 + 4

h(x) = 2x - 1/ x + 3

Find (f o h)(x)

(f o h)(x) = f(h(x))

f(2x-1/x +3) = (2x-1/x +3)^2 + 4

f(2x-1/x +3) = (4x^2 - 4x + 1/x^2 + 6x +9 ) + 4

Did I do this correctly?(Tmi)

Printable View

- January 27th 2009, 11:43 PMmoonman[SOLVED] (f o h)(x)
f(x) = x^2 + 4

h(x) = 2x - 1/ x + 3

Find (f o h)(x)

(f o h)(x) = f(h(x))

f(2x-1**/**x +3) = (2x-1**/**x +3)^2 + 4

f(2x-1**/**x +3) = (4x^2 - 4x + 1**/**x^2 + 6x +9 ) + 4

Did I do this correctly?(Tmi) - January 27th 2009, 11:54 PMMoo
- January 28th 2009, 12:02 AMmoonman